2013
DOI: 10.1007/s00253-013-5241-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration of polysaccharides from Agaricus subrufescens

Abstract: A simplified submerged airlift cultivation was established for the production of biomass from Agaricus subrufescens. In this work, soluble polysaccharides extracted from fungal mycelium, fruiting bodies, and the residual culture media were concentrated by nanofiltration. Total and high molar mass polysaccharides and soluble solids were determined in the concentrate for the three extracts. Additionally, the permeate flow, the influences of temperature and pressure, and the resistance to the permeate flow during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The genus Agaricus L., the type genus of the Agaricaceae contains important edible and medicinal species (Largeteau et al 2011;Wisitrassameewong et al 2012;Camelini et al 2013;Thawthong et al 2014). Significant examples are A. subrufescens Peck and A. bisporus (J.E.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Agaricus L., the type genus of the Agaricaceae contains important edible and medicinal species (Largeteau et al 2011;Wisitrassameewong et al 2012;Camelini et al 2013;Thawthong et al 2014). Significant examples are A. subrufescens Peck and A. bisporus (J.E.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it invariably increases energy costs (Listiarini et al 2009). Camelini et al (2013b) found that resistance caused by fouling alone was responsible for less than 3.5 % of the total resistance for the polysaccharide extracts. This is a remarkable result since this is the main problem faced by nanofiltration of such materials (M€ antt€ ari et al 2000).…”
Section: Extraction and Concentrationmentioning
confidence: 98%
“…Following the studies of Silveira et al (2012), Camelini et al (2013b) developed a process to separate polysaccharides extracted from A. subrufescens grown in airlift bioreactors. The main objective of that study was to produce large volumes of fungal biomass; extract the polysaccharide contents, both from the biomass and the culture media; and employ tangential flow nanofiltration to concentrate and purify these bioactive substances.…”
Section: Extraction and Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Major advantages of such system are its good sustainability, lower energy and material use and good productivity (Dalmau et al 2014;Larroche et al 2017). Examples are the production and recovery of functional polysaccharides (Mazzei et al 2010;Camelini et al 2013), lipase, rhamnolipid (Dhariwal thesis) peptides, gelatine and pectin (Lipnizki 2010), production of fatty acids (Chakraborty et al 2012) fructoolligosaccharides (Sanchez et al 2008), galactoglucomannan (Persson and Johnsson 2010), the enzymatic hydrolysis combined with selective ultrafiltration in processing of vegetable proteins (Dauffin et al 2001) and also other (Giorno et al 2017). Despite its obvious advantages, the process has a major drawback due to the problem of membrane fouling.…”
Section: Introductionmentioning
confidence: 99%